Le printemps à la portée des gestes. Danser le solo de l’élue dans Le sacre du printemps au XXIe siècle - Aurore Després (Ambiances, 2020)
Few scenic artworks raise the climatic and atmospheric issue in a such crucial way: after having celebrated earth and awaken winter, a community acclaims the Chosen One that will be ultimately sacrificed to make spring happen. Here lies he drama of The Rite of Spring (1913), in which converge all matters in Stravinski’s music, Nijinski’s dance and Roerich’s scenography. How will the Chosen One repel death surrounding her, in a gesture of birth, in order for spring to flow out? Can spring come from gestures? This article is based on archives of the renowned ballet, notably the famous critic of Jacques Rivière (1913) analyzing the esthetic atmosphere of the ballet, and essentially on the historical reconstruction of its choreography by Dominique Brun entitled Sacre #2 (2014), interpreted by Julie Salgues and on her own words about her gestures. This paper, also based on my present thoughts in a 2020 spring that seems unable to unfold, analyses the various compressions until reversal of the atmospheric regime and aims to contribute to a theory of atmospheres that would place in its center the notion of gesture and especially of “geste-milieu”.